Composição e distribuição espaço-temporal do ictioplâncton das lagoas Imboassica, Cabiúnas e Comprida, Macaé, RJ - Soares, Cláudio Lopes (1998)
Imboassica, Cabiúnas and Comprida lagoons are located in Macaé county, Southeastern Brazil which are differenciated through the frequency of the natural or artificial openings of the sand bar that separates them from the sea. Actually, Imboassica lagoon have frequent artificial openings; Cabiúnas lagoon have natural openings or scarrce artificial openings and Comprida lagoon don't have sand bar openings. Previous studies have shown that these openings changes the ichthyofauna composition This research tried to determine the variations on the quali-quantitative ichthyoplankton composition of the three lagoons, focusing on its spatial and temporal distribution during a one year period, relating those changes with salinity, temperature and sand bar openings. The collectings were done in pre-detenninate areas using superficial haulings with a plankton net. Extra collectings were done with manual and marginal haulings and a "big bolter", with the purpose of suggesting alternative techniques for ichthyoplankton collecting in coastal lagoons. Toe identification of the eggs was based in morphometric characters, getting to the conclusion that they belonged to Anchoa januaria and Anchovia clupeoides. Toe main larvae groups were A. januaria, Xenomelaniris brasiliensis and Platanichthys platana in Imboassica lagoon, P. platana in Cabiúnas lagoon and Hyphessobrycon bifasciatus in Comprida lagoon. This research ratifies the importance of Imboassica and Cabiúnas lagoons as growth areas for marine-estuarine species and con:firms the freshwater composition of Comprida lagoon.